Guide for Medical Services in Benghazi - Hamad Mohammed, Aya (The Libyan International Medical University - Faculty Of Information Technology, 2021)
It is difficult to search for places and addresses of health facilities in the city of Benghazi (specialized clinics, dental clinics, pharmacies, etc.). Besides that, the people who come from outside the city and not familiar with health services it is also difficult to find specialists, health care providers and their work schedules in any hospital he\she is available. Therefore, the aim of this project is to develop a website to provide a medical guide for Benghazi city, to facilitate the search for medical services. The techniques used in building the prototype of the website (Visual Studio, ASP.NET and SQL Server).